The complete mitochondrial genome of the smallest known free-living insect Scydosella musawasensis. Issue 1 (1st January 2016) - Nedoluzhko, Artem; Sharko, Fedor; Boulygina, Eugenia; Tsygankova, Svetlana; Sokolov, Alexey; Mazur, Alexander; Polilov, Alexey; Prokhortchouk, Egor; Skryabin, Konstantin
Abstract: The mitochondrial genome of the smallest known free-living insect Scydosella musawasensis (Polilov, 2015) is published in this paper. The mitochondrial DNA (mtDNA) is 14 719 base pairs (bp) in length and contained 13 protein-coding genes, 2 rRNA genes and 21 tRNA genes. The overall base composition of the genome in descending order was 40.59% – A, 13.85% – C, 36.82% – T and 8.73% – G, with a significant AT bias of 77.41%.